2000
DOI: 10.1161/01.res.87.9.760
|View full text |Cite
|
Sign up to set email alerts
|

Sinoatrial Node Pacemaker Activity Requires Ca 2+ /Calmodulin-Dependent Protein Kinase II Activation

Abstract: Abstract-Cardiac beating arises from the spontaneous rhythmic excitation of sinoatrial (SA) node cells. Here we report that SA node pacemaker activity is critically dependent on Ca 2ϩ /calmodulin-dependent protein kinase II (CaMKII). In freshly dissociated rabbit single SA node cells, inhibition of CaMKII by a specific peptide inhibitor, autocamtide-2 inhibitory peptide (AIP, 10 mol/L), or by KN-93 (0.1 to 3.0 mol/L), but not its inactive analog, KN-92, depressed the rate and amplitude of spontaneous action po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
211
3
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(228 citation statements)
references
References 31 publications
(27 reference statements)
13
211
3
1
Order By: Relevance
“…Surprisingly, I Ca facilitation was completely abolished in SR-AIP. In addition, I Ca recovery from inactivation, a process slowed by AIP [36,37] and by the synthetic CaMKII inhibitor KN-93 [35], was also markedly slowed in SR-AIP. Therefore our results suggest that the CaMKII inhibiting peptide located in the SR membrane inhibits CaMKIIdependent phosphorylation of the L-type Ca 2+ channel.…”
Section: Ca Facilitation Is Inhibited By Sr-targeted Camkii Inhibitionmentioning
confidence: 95%
See 1 more Smart Citation
“…Surprisingly, I Ca facilitation was completely abolished in SR-AIP. In addition, I Ca recovery from inactivation, a process slowed by AIP [36,37] and by the synthetic CaMKII inhibitor KN-93 [35], was also markedly slowed in SR-AIP. Therefore our results suggest that the CaMKII inhibiting peptide located in the SR membrane inhibits CaMKIIdependent phosphorylation of the L-type Ca 2+ channel.…”
Section: Ca Facilitation Is Inhibited By Sr-targeted Camkii Inhibitionmentioning
confidence: 95%
“…Both processes depend on CaMKII [21,22,24,36,37] but if the AIP moieties in the fusion protein anchored in the SR membrane cannot reach the sarcolemma these processes should be unaltered in SR-AIP mice. To rule out secondary effects on I Ca facilitation due to changes in intracellular Ca 2+ handling, we performed these experiments in the presence of 10 mM EGTA, therefore abolishing intracellular Ca 2+ transients.…”
Section: Ca Facilitation and Recovery From Inactivationmentioning
confidence: 99%
“…Interestingly, in rabbit SANC LCRs predominantly occur within a time window of ~20% of the cycle length before an excitation [10,14], i.e., exactly where "1:1 entrainment zone" was originally discovered [23]. Also, arrhythmic beating showing various alternation patterns can be observed in rabbit SANC when the SR clock is slowed by chelation of intracellular Ca 2+ [25], by disabling Ca 2+ release by ryanodine [7] or by inhibition of PKA signaling [5,26].…”
Section: The Rhythmic Intracellular Ca 2+ Clock Entrains Normal Autommentioning
confidence: 99%
“…TN-XXL expression, however, caused a reduced maximal heart rate under maximal adreneric stimulation, thus reducing the overall dynamic range of heart rate regulation. It is possible that overexpression of TN-XXL buffers Ca 2 + in SAN pacemaker cells, which is required to increase the slope of the pacemaker potential 41 and is utilized to support the physiological increase in heart rate. In line with this hypothesis it has been shown that chelating SAN Ca 2 + by EGTA 41 , BAPTA 41 or the Ca 2 + indicator Indo-1 (refs 42,43) significantly reduces the slope of diastolic depolarization and beating rate of sinoatrial pacemaker cells.…”
Section: Discussionmentioning
confidence: 99%